If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3+(-3x+4)-2(x+4)=43x
We move all terms to the left:
3+(-3x+4)-2(x+4)-(43x)=0
We add all the numbers together, and all the variables
-43x+(-3x+4)-2(x+4)+3=0
We multiply parentheses
-43x+(-3x+4)-2x-8+3=0
We get rid of parentheses
-43x-3x-2x+4-8+3=0
We add all the numbers together, and all the variables
-48x-1=0
We move all terms containing x to the left, all other terms to the right
-48x=1
x=1/-48
x=-1/48
| -7(x+2)=(6-4x)2-(-5+2) | | 165=75-x+100 | | (3x-15)(7.5-x)=0 | | 6m+5m+4=15m | | 3(x-3)-3=3 | | 10y+1=43 | | -0.03x^2+2.3x-20=0 | | 8x3=8x3= | | 8x3=8x3 | | -44.x=8 | | -40.x=-74 | | 2x+10=-8-7 | | 10m-4=22 | | 0,2=4/x | | 0,2=x/0,4 | | 0,2=0,4/x | | 3(x-3)-2(x-1)=7 | | a÷7=9 | | 5x+4x=32x= | | –7s+9=–6s | | 3x+6-x-1=9 | | xx7=35 | | a)8a+(5a+2)= | | 2x-153x+17=0 | | 3(a+5)=2a-39 | | 25=(14-y) | | 2,5x-9,1=-0,1+2,7x | | 25÷(14-y=) | | 2x+58/8=10 | | 2x+3x+90=360° | | 6x+14/4=10 | | 3x+40/2=2 |